Merit management web application - Krishnan, Kautham (2019)
Merit Management Desktop Application (MMDA) is a system for staffs to manage the merit in an easy, fast and authentic way to any of the event conducted by Universiti Malaysia Pahang (UMP) for students. The main play of the system is using biometric of the students to authenticate their attendance in an event which is their fingerprint. In the past years, students have cheated in many ways to get merit from the event. This is an illegal act in the university. Students who absent to the events takes advantage of other person to input merit for them as the currently used system could not verify the person’s identity before it could insert merit data into the database. MMWA breaks this chain of cheating by introducing biometrics into the cycle. Students could only input merit through their fingerprint and as fingerprint is unique to each person, the probability of cheating is near to impossible. Rapid Application Development (RAD) methodology is used to develop this system because it is a small project and only for prototype. The RAD makes the best fit for this type of criteria. The other functions consist of five which are registration, login, manage attendance, manage event and manage database. User Acceptance Test (UAT) is conducted after the system is completed to ensure that all the functions work properly to the requirement of the client. It verifies the objective of managing the merit for students are more secure and easier than before.